Prevalence and risk factors of mortality among heart failure patients in low resource setting hospitals: a multicenter prospective observational study - Firomsa Bekele; Tadesse Sheleme; Tesfaye Tsegaye; S. Angala Parameswari; Manjoor Ahamad Syed; Lalise Tafese; Wubishet Gezimu (Frontiers in Cardiovascular Medicine)
BackgroundHeart failure is a significant worldwide health problem that leads to mortality. Therefore, this study aimed to evaluate treatment outcomes and associated factors of heart failure patients who were admitted to hospitals in the southwest of Ethiopia.Methods and participantsA multicenter prospective observational study was conducted from 1 February to 1 August 2021. Drug therapy problems were assessed as per the Cipolle, Strands, and Morley drug therapy problems classification method. The drug therapy was registered by using the drug-related problem registration format. The results of logistic regression analysis was interpreted as crude odds ratio and adjusted odds ratio (AOR) at 95% confidence interval (CI) to determine the association between dependent and independent variables.ResultsIn our study settings, a total of 205 (85.1%) heart failure patients showed improvement and 36 (14.9%) died at hospital discharge. Being ≥65 years (AOR = 7.14, 95% CI: 2.04–.25.01, P = 0.002), a previous hospitalization (AOR = 6.20, 95% CI: 1.81–21.21, P = 0.004), and the presence of medication-related problems (AOR = 3.65, 95% CI: 1.13–11.73, P = 0.03) were the predictors of mortality.ConclusionThe prevalence of in-hospital mortality among heart failure patients was found to be high. Previous hospitalization, older age, and the presence of drug therapy problems were the predictors of mortality among heart failure patients. Therefore, proper attention should be given to the management of elderly and re-admitted heart failure patients in addition to their regular care. In addition, hospitals should implement clinical pharmacy services to address any drug-related problems.